(untitled) (ENTHYMEMA, 2020)
This essay focuses on the different forms and values of tautology in Italian poetry from the 1990s until today. I have identified a ‘dysphoric’ tautology, where the poet mainly focuses on what is missing (a transcendence, a further meaning beyond the simple existence of a thing), as opposed to an ‘euphoric’ tautology, where on the contrary the poet mainly focuses on what is present (the full presence, free from additional meanings, of the thing). There are other oppositions connected to the fundamental one: tautology and lack of communication (one being can only talk for itself and understand only itself) vs tautology and possibility of communication (the simple perception of the ‘bare thing’ allows to find a common ground to understand each other); tautology and standardization (tautology as a figure of a reality which can only repeat itself) vs tautology and defamiliarization (tautology as a moment of new perception).